Postharvest preservation of fruits and vegetables by natural based edible coatings – A review - Nguyen, Hang Nga; Dao, Van Hoang; Nguyen, Thi Minh Tu; Pham, Thi Van Anh (Vietnam Journal of Biotechnology, 2025)
The market demand for fruits and vegetables is substantial due to their high nutritional value. However, their perishable nature results in relatively short shelf life. Approximately 40% of produce is lost due to damage from insects, microorganisms, and adverse conditions during harvesting, transportation, and storage. Consequently, preservation of fruits and vegetables presents a significant global challenge. Various preservation methods have been applied to fruits and vegetables, with particular interest in biopolymers (polysaccharides, proteins, lipids, etc.) and their combinations with plant-derived products that possess diverse biological activities, renewability, and environmental compatibility. These coatings act as protective barriers, reducing moisture loss, delaying ripening, and inhibiting microbial growth, thereby extending the shelf life of produce. Polysaccharides such as chitosan, alginate, and cellulose derivatives are widely used due to their film-forming properties and biocompatibility. Proteins like gelatin and casein, as well as lipids such as beeswax and carnauba wax, are also employed to enhance the mechanical and barrier properties of the coatings. Additionally, plant-derived compounds such as essential oils, polyphenols, and flavonoids are incorporated into these coatings to provide antioxidant and antimicrobial benefits, further improving preservation efficacy. By leveraging the potential of biopolymers and plant-derived compounds, the development of advanced edible coatings can significantly contribute to the global effort to preserve perishable produce and meet the increasing demand for fresh and nutritious fruits and vegetables.This review presents the applications of natural edible coatings for postharvest preservation of fruits.